Beach Resort of Tawa-Tawaro in East Kolono Subdistrict, South Konawe Regency: An Eco-Architectural Approach - Aldiansyah, Sandi; Nahdatunnisa, Nahdatunnisa; Nurbaity, Dian Puteri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Tawa-Tawaro Beach has emerged as one of the prominent tourist destinations in East Kolono. This area holds significant potential for tourism development owing to its natural allure and stunning panoramas, attracting frequent visits from locals and tourists alike. However, several challenges persist, including inadequate organization of the area, limited accommodation options, and environmental issues such as poor waste management systems and the absence of electricity infrastructure. Consequently, there is a pressing need for the design of a beach resort that offers accommodation facilities catering to the needs of travelers. In this study, a qualitative descriptive approach is employed. The objective is to enhance the organization of the area while considering ecological architectural aspects and elements, thus ensuring that visitors are provided with improved facilities.